THE IMPACT OF PRODUCT VARIATION, PRODUCT QUALITY, AND SERVICE QUALITY ON PURCHASE DECISION OF KO-KOPIAN PRODUCTS - Noah Jonathan Satria Wicaksono; J.E Sutanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Abstract: The research which entitled